Is There (Still) a Place for Sequential Conditioning? - Boris Bours; Stavroula Masouridi-Levrat (Current Oncology)
There is still an unmet need for the treatment of high-risk hematological malignancies. To date, allogeneic stem cell transplantation remains the only chance of cure. Most patients suffering from high-risk hematological malignancies are of an older age and often present with comorbidities. Moreover, patients achieving remission often suffer from early relapse. Amongst the different treatment options, sequential conditioning has yet to prove its value against other conditioning regimens. Sequential conditioning relies on a short course of intensive chemotherapy that is quickly followed by immunosuppressive conditioning before allogeneic stem cell transplantation. Here, we will try to determine which patients can benefit from sequential conditioning. Amongst the different sequential regimens, we will also try to assess if one regimen is better than all the others. Despite the several studies conducted on sequential conditioning, very few are prospective work and head-to-head comparisons are almost inexistant. Sequential conditioning also relies on the use of prophylactic donor lymphocyte infusion post-transplantation. Hence, limiting non-relapse complications is of primary importance to the allow administration of post-transplant treatment. In the era of new targeting therapies, is there still a place for sequential conditioning? Can patients benefit from an association of new therapeutic agents and sequential conditioning?